(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2022)
Background: Intrauterine devices (IUDs) are long-acting reversible contraceptives that are widely used due to their effectiveness and safety profile. Complications associated with IUD insertion or removal are rare but can be fatal. Case presentation: A 36-year-old para 3+0 presented to the accident and emergency department with per vaginal bleeding and signs of an acute abdomen following three failed attempts to remove an IUD inserted two weeks prior. Ultrasound imaging revealed marked hemoperitoneum, and an IUD embedded in the left ovary. An exploratory laparotomy revealed that the IUD was embedded on the left ovary with multiple perforations on the uterus and ileum. The IUD was removed, and the perforations were repaired. Her condition deteriorated and she succumbed to refractory septic shock two days later. Conclusion: The presented patient succumbed to complications resulting from injuries caused by an IUD. Blind procedures to remove displaced IUDs should be avoided especially where previous attempts have failed.